Two new species of Boesenbergia (Zingiberaceae), from Sabah, Malaysia - Lam, Nyee Fan; Halijah Ibrahim; Sam, Yen Yen; Rozainah Mohammad Zakaria; Axel Dalberg Poulsen (Pensoft Publishers, 2022)
Two new species of Boesenbergia, B. sugudensis sp. nov. and B. truncata sp. nov. were discovered in Sabah, Malaysian Borneo. Boesenbergia sugudensis resembles B. imbakensis in that the leaf sheath of the plant is not thickened and in the anther thecae dehiscing by longitudinal slits, but differs in having a longer petiole and tubular calyx. Boesenbergia truncata resembles B. orbiculata by the short petiole and a bilobed calyx, but differs by the truncate leaf base, the acute leaf apex, opposite leaves with a narrower lamina parallel to the ground and anther thecae dehiscing by pores. The new species are described and illustrated in detail.